2015
DOI: 10.1371/journal.pone.0132248
|View full text |Cite
|
Sign up to set email alerts
|

Deep Characterization of the Microbiomes of Calophya spp. (Hemiptera: Calophyidae) Gall-Inducing Psyllids Reveals the Absence of Plant Pathogenic Bacteria and Three Dominant Endosymbionts

Abstract: Bacteria associated with sap-feeding insect herbivores include not only symbionts that may increase their hosts’ fitness but also harmful plant pathogens. Calophya spp. gall-inducing psyllids (Hemiptera: Calophyidae) are being investigated for their potential as biological control agents of the noxious weed, Brazilian peppertree (Schinus terebinthifolia), in Florida. Although there are no examples of plant pathogen transmission by members of the family Calophyidae, several insects in the superfamily Psylloidea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 60 publications
4
22
0
Order By: Relevance
“…B. tabaci is a phloem-feeding insect pest characterized by high fecundity, short developmental time, significant dispersal capability, and ability to use multiple plants as hosts [11]. Previous culture-independent approaches have reported that B. tabaci, as other sternorrhynchan insects (psyllids and aphids), presents low (if any) variety of gut-associated ectosymbionts [10,12,13]. This low diversity was mainly attributed to the sternorrhynchan simple gut morphology, the nearly microbial-free diet (phloem), the ability of the insects to digest the food quickly, and the presence of intracellular bacteria, also called endosymbionts, that might compete for the host resources [6,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. tabaci is a phloem-feeding insect pest characterized by high fecundity, short developmental time, significant dispersal capability, and ability to use multiple plants as hosts [11]. Previous culture-independent approaches have reported that B. tabaci, as other sternorrhynchan insects (psyllids and aphids), presents low (if any) variety of gut-associated ectosymbionts [10,12,13]. This low diversity was mainly attributed to the sternorrhynchan simple gut morphology, the nearly microbial-free diet (phloem), the ability of the insects to digest the food quickly, and the presence of intracellular bacteria, also called endosymbionts, that might compete for the host resources [6,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous culture-independent approaches have reported that B. tabaci, as other sternorrhynchan insects (psyllids and aphids), presents low (if any) variety of gut-associated ectosymbionts [10,12,13]. This low diversity was mainly attributed to the sternorrhynchan simple gut morphology, the nearly microbial-free diet (phloem), the ability of the insects to digest the food quickly, and the presence of intracellular bacteria, also called endosymbionts, that might compete for the host resources [6,12,13]. All whiteflies, including B. tabaci, harbor an obligatory endosymbiont named Portiera aleyrodidarum and different facultative endosymbionts, including the genera Hamiltonella, Arsenophonus, Rickettsia, Wolbachia, and Cardinium [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…C. ruddii," psyllids can associate with other bacteria as revealed by several microbial surveys. In some of these studies, bacterial communities associated with psyllids were not very diverse (Subandiyah et al, 2000;Nachappa et al, 2011;Raddadi et al, 2011;Fagen et al, 2012;Overholt et al, 2015), while other surveys found a greater diversity of bacteria associated with psyllids (Hail et al, 2012;Arp et al, 2014). Subsequent studies identified potential roles of secondary endosymbionts in psyllid reproduction, climate and host adaptation, and pathogen transmission.…”
Section: Association Psyllids-bacteriamentioning
confidence: 99%
“…For example, Wolbachia were found associated with several populations of D. citri in Florida (Subandiyah et al, 2000;Hert et al, 2008;Fagen et al, 2012;Saha et al, 2012;Hoffmann et al, 2014;Chu et al, 2016), China Ma et al, 2012), Iran and Pakistan (Lashkari et al, 2014), and Brazil (Guidolin & Consoli, 2013). Wolbachia were also found associated with populations of B. cockerelli (Nachappa et al, 2011;Hail et al, 2012;Arp et al, 2014), Cacopsylla pruni (Duron, 2013) and with nonvector gall-inducing psyllids in the genus Calophya (Hemiptera: Calophyidae) (Overholt et al, 2015).…”
Section: Association Psyllids-bacteriamentioning
confidence: 99%
“…These methods are based on the deep sequencing of PCR-amplified bacterial 16S rRNA gene fragments, and the sequence data generated by HTS techniques are usually grouped into the same operational taxonomic unit (OTU) based on sequence similarity (≥97%), enabling the detection of all bacterial species existing in various samples. OTU is an effective tool for exploring bacterial communities, such as the symbiosis in aphids and psyllidae (Gauthier, Outreman, Mieuzet, & Simon, 2015;Hao & Chen, 2012;Jousselin et al, 2016;Overholt, Diaz, Rosskopf, Green, & Overholt, 2015). Therefore, HTS techniques are the first choice for studying the diversity of microbial communities (Degnan & Ochman, 2012).…”
mentioning
confidence: 99%